Slope Stability Evaluation and Geometrical Recommendation Using The Morgenstern Price Method - Matius Sesa, Heri; Najib, Najib; Luthfi Dalimunthe, Hasnan; Handietri, Zerlinda (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
The study is located on PT Indocement Tunggal Prakarsa Tbk., which is still actively engaged in mining operations. The study aimed to determine the slope Safety Factor (SF) and offer suggestions for safe slope geometry for mining operations. Primary data collection through observation of lithology conditions, sample testing in the laboratory, scanline mapping, slope geometry measurements, and secondary data obtained from company inventories and related sources. The kinematic approach is used to assess the risk of landslides. This slope stability study uses boundary equilibrium based on the Morgenstern Price and Mohr-Coulomb failure criteria. Limestone is the majority of the rocks in the location. The kinematic analysis demonstrated that direct toppling and wedge toppling are the landslide potential at the research location. Using the non-circular boundary equilibrium approach, slope stability analysis was carried out on four Regions with dry and saturated groundwater conditions i.e, Regions A', B140, C120, and C135. The four Regions have stable slopes and are in good condition (SF values over 1.25). For the excavation to be carried out optimally, the recommendations for optimization of the overall slope geometry are given, namely, the height of the bench is 10 m, and the width of the ladder is 4 m. The slope angle is 80o, with SF value of 3.035 in dry conditions and an SF value of 2.021 in saturated conditions.